La memorialística valenciana del segle XIX: dietaris, memòries i altres anotacions. Un panorama actualitzat. - ZALBIDEA, ALAITZ (Scripta)
The present work aims to offer a new overview of Valencian memoir literature of the 19th century and to remark the importance of these kind of documents in our history. This study gathers diaries, collections of memoirs or notes of unknown or difficult-to-access events, as well as others that have already been transcribed, edited and studied that have not received the necessary attention or been taken into account in the Valencian memoir corpus. Furthermore, it is noted, as some researchers have already stated, that from the end of the 18th century until the first third of the 20th century no diary or memoir had been written in Valencian, except in some cases in which is used occasionally in some private document.